Mobile messenger application: Sharing, rating and engagement in global social commerce - Lee, Cheng Ean Catherine *; Teh, Phoey Lee * (Lectito, 2016)
This paper explores the relationship between rating, sharing and engagement within the freely available Mobile Messaging Application (MMA) through understanding their features and compatibility. We argued that MMA has the potential to substitute online marketing communication in the near future and the use of closed group chatting, sharing of information, and mobile-commerce in marketing communication has increased. Therefore, reviews on the current MMA, their abilities, compatibilities, functions and features with the marketing communication functions and features were analyzed. In particular, this study focuses on the implementation of MMA in future marketing communication and the engagement of users in sharing information, commenting on products and rating (sharing opinion) on products and services.